Offshore wind-turbine structures: a review - O'Kelly, Brendan (My University, 2013)
This paper reviews various issues related to wind-power generation, one of the more popular forms of renewable energy, including attractions and challenges of electric power generation through onshore and offshore resources. Significant increases in wind-turbine dimensions, rated power-generation capacity and size of wind farm developments over the past two decades are projected to continue. Offshore wind-power generation presents many engineering challenges including: limited guidelines available for analysis and design of foundation/support structures; inadequate logistics for construction/fabrication; and comparatively expensive operation and maintenance costs, which combined result in current levelised cost of energy approximately double that for onshore wind-power generation. Different offshore foundation options are discussed in terms of general layout, loading characteristics and related fundamental natural frequency. Outlooks for some new approaches/developments and areas for further research are identified that may go towards reducing the levelised cost of energy for wind-power generation more in line with that from other energy resources, thereby enhancing the attractiveness of this industry for potential investors.
PUBLISHED
Themed issue on 'Wind turbine foundations'
Keywords: foundations; offshore engineering; renewable energy